Cardiorenal syndrome: therapeutical challenge - Lopes, Sara Cristina Cerqueira (2016)
Cardiorenal syndrome is described by the coexistence of cardiac and renal disease on the same individual, and it can affect both dogs and cats. The most consensual definition describes it as a “pathophysiologic disorder of the heart and kidneys whereby acute or chronic dysfunction of one of the organs causes acute or chronic dysfunction of the other”. The interest, recognition of the importance and prevailing of this syndrome in veterinary medicine has grown and, recently, a committee of veterinarians specialized in cardiology and nephrology proposed that cardiorenal syndrome would be further designated as cardiovascular-renal axis disorders, classifying it in three types according to the disorders primary cause: CvRDH to heart as the primary failing organ, CvRDK to kidneys as the primary failing organ and CvRDO to when it has other causes. The current therapeutic for cardiorenal syndrome presents many variations, depending on the veterinarian preference as for what drugs should be used. However, there are certain assumptions that must be considered regarding this therapeutic challenge, and shouldn’t be undervalued since they take serious effect on the therapeutics success and, therefore, on the animal life expectancy. The dosages for the drugs used must suffer constant review, together with careful monitoring to the patients cardiac and renal functions, since the main challenge relies on the attempt to improve at the most one the organs function, without causing damage, or deterioration, to the other. This dissertation objective is to revise the current state of knowledge of cardiorenal syndrome in small animals, focusing on its diagnosis, classification and therapeutic challenge.